Frailty in the Elderly - Understanding and Managing Complexity 2021
DOI: 10.5772/intechopen.92122
|View full text |Cite
|
Sign up to set email alerts
|

Elderly and Polypharmacy: Physiological and Cognitive Changes

Abstract: Population ageing is one of the most significant social transformations of the twenty-first century. The increase in average life expectancy was a successful challenge achieved in the modern world. However, nowadays a new challenge arises for all society: achieving a better quality of life for increasing people’s life. The comorbidities associated with ageing make elderly prone to polypharmacy. On the other hand, physiological and cognitive changes interfere with drugs’ pharmacodynamics and pharmacokinetics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Contrary to our clinical hypothesis, no significant correlation was observed between obesity and a prolonged LOS [ 7 - 9 ]. Similar studies have shown no statistically significant difference between patients with and without obesity and postoperative morbidity [ 10 ]. Moreover, a recent meta-analysis of 19 studies established that there was no significant difference in 30-day mortality or postoperative complications between patients with and without obesity [ 11 ].…”
Section: Discussionmentioning
confidence: 68%
“…Contrary to our clinical hypothesis, no significant correlation was observed between obesity and a prolonged LOS [ 7 - 9 ]. Similar studies have shown no statistically significant difference between patients with and without obesity and postoperative morbidity [ 10 ]. Moreover, a recent meta-analysis of 19 studies established that there was no significant difference in 30-day mortality or postoperative complications between patients with and without obesity [ 11 ].…”
Section: Discussionmentioning
confidence: 68%
“…Drug interactions, common in polypharmacy, can cause synergistic toxicity and thus be risk factors, such as the combination of corticosteroids and NSAIDs. Polypharmacy leads to problems in medication adherence and correct administration representing a risk for adverse events or ADR [31,36,37].…”
Section: The Healthcare Impact Of Adr In Older Patientsmentioning
confidence: 99%
“…Associating these criteria with information management tools such as Clinical decision support systems [CDSS] can allow improvements in patient therapy. These CSSDs, usually computerized, can verify interactions between medicine-disease or medicine-medicine, also detecting PIM [36].…”
Section: Potentially Inappropriate Medication For Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging involves pharmacokinetic and pharmacodynamic changes. 1 Older adults have a reduced ability to adjust to external environmental changes, increased susceptibility to disease, and a reduced ability to recover, which leads to a modified drug response and greater vulnerability to adverse drug reactions. 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%